A Bright Start :The experience of an Aberdeen primary school introducing the Bright Start cognitive curriculum - Sarah Philp; Emma Powell; Melissa Mitchell (University of Aberdeen, School of Education, 2009)
This article by Sarah Philp (Depute Principal Educational Psychologist), Emma Powell and Melissa Mitchell (Educational Psychology Assistants for Research) summarises the experience of an Aberdeen Primary School which introduced the Bright Start cognitive curriculum. The aim of this project was to focus on the experience of the staff involved in the Primary School and to consider what would be helpful to other schools or individuals interested in using Bright Start.